22.1k views
0 votes
Step by step instructions

Step by step instructions-example-1
User Henhuy
by
5.0k points

1 Answer

6 votes

If our two roots are
r and
s we can write


0 = (x-r)(x-s) = x^2 + bx + 6


x^2 -(r+s)x+rs = x^2 + bx + 6

Matching coefficients,


-(r+s) = b


rs = 6

"Positve integral" is a fancy way of saying natural number, 1, 2, 3, ...

So these are the factors pairs of six:


6=1 \cdot 6 = 2 \cdot 3

The two possible sums are 1+6=7 and 2+3=5. b is the negative sum.

Answer: b=-7 or b=-5

User Melody Horn
by
5.7k points